Three-Year Follow-Up of Results of Intraocular Lens Fixation in Patients with Retinitis Pigmentosa - Gen Miura; Takayuki Baba (Case Reports in Ophthalmology, 2023)
This is a retrospective, consecutive, noncomparative case series of 6 eyes of 5 retinitis pigmentosa (RP) patients who had undergone pars plana vitrectomy (PPV) and intraocular lens (IOL) implantation. The aim of this case series was to report the long-term outcomes of PPV with IOL implantation in patients with RP). The surgical procedures, visual function, refractive error, corneal endothelial cell density, intraocular pressure, and retinal morphology were evaluated before and 3 years after the surgery. Six eyes of 5 RP patients that had undergone PPV and IOL implantation with or without suturing for lens dislocation were studied. The visual acuity was maintained or improved at 3 years after surgery in all 6 eyes. No intraoperative complications occurred in any of the cases. The mean deviation of the Humphrey Field Analyzer 10–2 program and the retinal morphology evaluated by optical coherence tomography did not show any abnormal changes before and after surgery. In two eyes, the postoperative refractive error was more myopic than the attempted refractive error. In conclusion, PPV with IOL implantation can be performed safely in RP patients, and the long-term visual acuity can be maintained.